2012
DOI: 10.1001/archdermatol.2012.3022
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib-Induced Paronychia

Abstract: Background: Paronychia has been reported in as many as 10% of patients treated with gefitinib. Although conservative management and treatment with topical or systemic antibiotics are beneficial, no effective method exists for intractable cases. Platelet-rich plasma (PRP) consists of a high concentration of platelets that promote wound healing through chemotaxis, cell proliferation, angiogenesis, and tissue remodeling. Observations: We herein report a refractory case of gefitinib-induced paronychia successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…İleri evre, RET füzyonu pozitif KHDAK' de, sistemik tedaviye ihtiyaç duyan RET mutasyonu pozitif 12 yaş ve üstü ileri evre medüller tiroid kanseri ve radyoaktif iyot tedavisine yanıt vermeyen veya radyoaktif iyot tedavisi için uygun olmayan RET füzyonu pozitif sistemik tedavi gerektiren 12 yaş ve üzerindeki RET füzyon pozitif ileri evre tiroid kanseri tedavisinde kullanılır. Önerilen selperkatinib dozu 50 kg'ın altındaki hastalar için 120 mg ve 50 kg veya üzeri hastalar için 160 mg' dır (104). Plazma proteinlerine %97 oranında bağlanır.…”
Section: Selperkatinibunclassified
“…İleri evre, RET füzyonu pozitif KHDAK' de, sistemik tedaviye ihtiyaç duyan RET mutasyonu pozitif 12 yaş ve üstü ileri evre medüller tiroid kanseri ve radyoaktif iyot tedavisine yanıt vermeyen veya radyoaktif iyot tedavisi için uygun olmayan RET füzyonu pozitif sistemik tedavi gerektiren 12 yaş ve üzerindeki RET füzyon pozitif ileri evre tiroid kanseri tedavisinde kullanılır. Önerilen selperkatinib dozu 50 kg'ın altındaki hastalar için 120 mg ve 50 kg veya üzeri hastalar için 160 mg' dır (104). Plazma proteinlerine %97 oranında bağlanır.…”
Section: Selperkatinibunclassified
“…Propranolol 1% cream and 0.5% topical timolol gel have been used more recently (Cubiró et al, 2018, Piraccini et al, 2016). One study demonstrated efficacy with platelet-rich plasma in treatment of recalcitrant paronychia from EGFR inhibitor therapy (Kwon et al, 2012). In refractory cases, nail plate avulsion or surgical debridement may be required for painful ingrown nails (Gilbar et al, 2009).…”
Section: Targeted Therapiesmentioning
confidence: 99%